Understanding social media usage at work from the perspective of social capital theory - Kasim, Nur Muneerah; Fauzi, M. A.; Wider, Walton; Yusuf, Muhammad Fakhrul (MDPI, 2022)
With the pervasive use of social media (SM) in organizations, it is regarded as a relevant driver that can influence an employee’s job performance. This study fills in the gap that extends the job performance concept by discovering the role of SM in innovative performance in introducing new ideas beyond standard specifications to produce novel and valuable organizational outcomes. By adopting the social capital theory (SCT), the present study investigates the roles of social media use at work in predicting social capital (network ties, shared vision, and trust) that might promote work engagement and subsequently affect employees’ innovative job performance. The data was collected through an online survey, and 291 Malaysian employees participated. The partial least square structural equation modelling (PLS-SEM) technique was applied in data analysis for the measurement model and structural model used in this study. Findings show that SM use at work significantly predicts network ties, shared vision, and trust. Besides, network ties and trust positively promoted work engagement except for shared vision. Subsequently, work engagement was associated with innovative job performance. This study provides theoretical and practical implications for extending knowledge, as well as mitigating plans and efforts to resolve employees’ performance concerning the issues of SM use at work.